Meiotic recombination provokes functional activation of the p53 regulatory network. - Lu, W.J.; Chapo, J.; Roig, I.; Abrams, J.M. (Science, 2010)
The evolutionary appearance of p53 protein probably preceded its role in tumor suppression, suggesting that there may be unappreciated functions for this protein. Using genetic reporters as proxies to follow in vivo activation of the p53 network in Drosophila, we discovered that the process of meiotic recombination instigates programmed activation of p53 in the germ line. Specifically, double-stranded breaks in DNA generated by the topoisomerase Spo11 provoked functional p53 activity, which was prolonged in cells defective for meiotic DNA repair. This intrinsic stimulus for the p53 regulatory network is highly conserved because Spo11-dependent activation of p53 also occurs in mice. Our findings establish a physiological role for p53 in meiosis and suggest that tumor-suppressive functions may have been co-opted from primordial activities linked to recombination.